The Lifecycle of Protests in the Digital Age - Pierre C. Boyer; Germain Gauthier; Yves Le Yaouanq; Vincent Rollet; Benoît Schmutz-Bloch (CESifo GmbH, 2024)
We propose a theory of protest dynamics with heterogeneous protest technology and intensity. The ability to mobilize online reduces the likelihood of coordination failures at both the extensive (engagement) and intensive (violence) margins. Social media can initially help launch massive protests, but then encourage radical factions to turn violent and drive out moderates. Using both online and offline data, we show that the 2018 Yellow Vest uprising in France followed such a crowd-in-then-crowd-out sequence: early online and offline mobilizations reinforced each other, but online discussions quickly radicalized, moderates left, and a handful of violent protesters took over the streets.
Keywords: D72; D74; L82; Z13; 330; protests; learning traps; crowding-out; violence; social media; NLP